Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve for the square root of \(-28\), we need to handle the square root of a negative number, which involves imaginary numbers. Here's the step-by-step solution:
1. Identify the negative aspect:
The number under the square root is \(-28\), which is negative. We know that the square root of a negative number involves the imaginary unit \(i\), where \(i = \sqrt{-1}\).
2. Express the negative number using \(i\):
Rewrite \(-28\) as \(-1 \times 28\).
3. Separate the components under the square root:
Using the property of square roots that \(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\), we have:
[tex]\[ \sqrt{-28} = \sqrt{-1 \times 28} = \sqrt{-1} \times \sqrt{28} \][/tex]
4. Simplify the square root of \(-1\):
We know that \(\sqrt{-1} = i\).
5. Simplify the square root of \(28\):
The number \(28\) can be factored into its prime factors as \(28 = 4 \times 7\). Thus:
[tex]\[ \sqrt{28} = \sqrt{4 \times 7} = \sqrt{4} \times \sqrt{7} \][/tex]
Since \(\sqrt{4} = 2\), this simplifies to:
[tex]\[ \sqrt{28} = 2\sqrt{7} \][/tex]
6. Combine the results:
Now, substituting back into our expression, we have:
[tex]\[ \sqrt{-28} = \sqrt{-1} \times \sqrt{28} = i \times 2\sqrt{7} \][/tex]
7. Write the final answer:
Simplifying the multiplication gives us:
[tex]\[ \sqrt{-28} = 2\sqrt{7}i \][/tex]
Thus, the square root of [tex]\(-28\)[/tex] is [tex]\(2\sqrt{7}i\)[/tex].
1. Identify the negative aspect:
The number under the square root is \(-28\), which is negative. We know that the square root of a negative number involves the imaginary unit \(i\), where \(i = \sqrt{-1}\).
2. Express the negative number using \(i\):
Rewrite \(-28\) as \(-1 \times 28\).
3. Separate the components under the square root:
Using the property of square roots that \(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\), we have:
[tex]\[ \sqrt{-28} = \sqrt{-1 \times 28} = \sqrt{-1} \times \sqrt{28} \][/tex]
4. Simplify the square root of \(-1\):
We know that \(\sqrt{-1} = i\).
5. Simplify the square root of \(28\):
The number \(28\) can be factored into its prime factors as \(28 = 4 \times 7\). Thus:
[tex]\[ \sqrt{28} = \sqrt{4 \times 7} = \sqrt{4} \times \sqrt{7} \][/tex]
Since \(\sqrt{4} = 2\), this simplifies to:
[tex]\[ \sqrt{28} = 2\sqrt{7} \][/tex]
6. Combine the results:
Now, substituting back into our expression, we have:
[tex]\[ \sqrt{-28} = \sqrt{-1} \times \sqrt{28} = i \times 2\sqrt{7} \][/tex]
7. Write the final answer:
Simplifying the multiplication gives us:
[tex]\[ \sqrt{-28} = 2\sqrt{7}i \][/tex]
Thus, the square root of [tex]\(-28\)[/tex] is [tex]\(2\sqrt{7}i\)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.